(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Disabled persons have traditionally been stigmatized bysociety. For long they have been subjected to systematic discrimination andneglect. Persons with disabilities must share the same rights as are enjoyed byall human beings. In this paper, we have discussed the sociological study ofrehabilitation needs of orthopedically handicapped people in India. In India, accordingto the census 2001, there were 21,906,769 thousand people with disability whoconstituted 2.13 percent of the total population. Out of 21,906,769 people withdisabilities, 12,605,635 were males and 9,301,134 were females and theseincluded persons with visual, hearing, speech, locomotors and mentaldisabilities. In contrast, the National Sample Survey Organization (NSSO)estimated that the number of persons with disabilities in India is 1.8 percentof the Indian population. The difference in the estimates of the census andNSSO for different types of disabilities can be explained by the lack ofuniversal definition. The prevalence of disability is marginally higher amongmales than among females throughout the world. The understanding of variousprogrammes and policies related to the rehabilitation and welfare for disabledpeople in India has been taken in detail. The Government of India hasimplemented numbers of policies and schemes for disabled people for theirrehabilitation and education.